Efficacy and safety of ixekizumab in patients with active psoriatic arthritis with and without concomitant conventional disease-modifying antirheumatic drugs: SPIRIT-P1 and SPIRIT-P2 3-year results - Coates, L; Mease, P; Kronbergs, A; Helt, C; Sandoval, D; Park, SY; Combe, B; Nash, P; Deodhar, A (Springer, 2022)
Introduction/Objectives: To evaluate the 3-year efficacy and safety of ixekizumab with and without concomitant conventional synthetic disease-modifying antirheumatic drug (csDMARD) use in patients with active psoriatic arthritis (PsA).